Razvoj kontejnerizacije u pomorstvu svijeta
Some thirty years passed since the commencement of a more vigorous development of modern container vessels. Up to this point of time we have had operating four generations of container vessels while the fifth, still more modern one is in the process of preliminary designing activities. In the period of 1970-1989 liner (general) cargo that lends to containerization reported a 300% increase (ba three times